Cultural issues in translating Indonesian words into English in Perahu Kertas Novel (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
A novel is a literary work that frequently uses cultural items. Therefore, translating a novel requires specific strategies. This paper aims to investigate (1) aspects of translating cultural words in the Perahu Kertas novel and (2) the acceptability of the translated version of the cultural words. This descriptive qualitative research collected the data using a note-taking technique. The collected data were then analyzed using the textual comparison theory (Apostolatu & Apostolatu, 2012). This study has revealed that aspects of translating cultural words in the novel are cultural equivalence, literal translation, expansion of meaning, omission elements, remaining, and transformation. These aspects have successfully presented the cultural items from SL into TL and effectively maintained cultural items in the SL by not translating the items in the TL.